Bleomycin-Induced Lung Injury Increases Resistance to Influenza Virus Infection in a Type I Interferon-Dependent Manner - Seo, Sang-Uk; Jeong, Jae-Hyeon; Baek, Bum-Seo; Choi, Je-Min; Choi, Youn Soo; Ko, Hyun-Jeong; Kweon, Mi-Na (Frontiers in Immunology, 2021)
Acute lung injury (ALI) results in acute respiratory disease that causes fatal respiratory diseases; however, little is known about the incidence of influenza infection in ALI. Using a ALI-mouse model, we investigated the pro-inflammatory cytokine response to ALI and influenza infection. Mice treated with bleomycin (BLM), which induces ALI, were more resistant to influenza virus infection and exhibited higher levels of interferon -I (IFN-I) transcription during the early infection period than that in PBS-treated control mice. BLM-treated mice also exhibited a lower viral burden and reduced pro-inflammatory cytokine production and neutrophil levels. In contrast, BLM-treated IFN-I receptor 1 (IFNAR1)-knockout mice failed to show this attenuated phenotype, indicating that IFN-I is key to the antiviral response in ALI-induced mice. The STING/TBK1/IRF3 pathway was found to be involved in IFN-I production and the establishment of an anti-viral environment in the lung. The depletion of plasmacytoid dendritic cells (pDCs) reduced the effect of BLM treatment against influenza virus infection, suggesting that pDCs are the major source of IFN-I and are crucial for defense against viral infection in BLM-induced lung injury. Overall, this study showed that BLM-mediated ALI in mice induced the release of double-stranded DNA, which in turn potentiated IFN-I-dependent pulmonary viral resistance by activating the STING/TBK1/IRF3 pathway in association with pDCs.